Cover Image. (25th November 2021) - Erbilgin, Nadir; Zanganeh, Leila; Klutsch, Jennifer G.; Chen, Shih‐hsuan; Zhao, Shiyang; Ishangulyyeva, Guncha; Burr, Stephen J.; Gaylord, Monica; Hofstetter, Richard; Keefover‐Ring, Ken; Raffa, Kenneth F.; Kolb, Thomas
Abstract : The cover image is based on the Original Article Combined drought and bark beetle attacks deplete non‐structural carbohydrates and promote death of mature pine trees by Nadir Erbilgin et al., https://doi.org/10.1111/pce.14197 .